The equity of admissions to the university hospital of Brasilia - Ireland, M.; Ribeiro, M.; Ali, Mohammed (Australasian Medical Journal Pty Ltd, 2015)
Background: Brazil has a highly stratified population with large socioeconomic disparities, as evidenced by marked differentiation in health status and access to health services by the population. In addition, the fact that the universal national health care system and a liberalised private care model exist side by side leads to increasingly inequitable health outcomes. Aims: This study aims to appraise the equity of access to the University Hospital in Brasilia, Brazil, in 2013. Methods: This study was a quantitative analysis of hospital admissions data. The sample included all patients admitted over a six-month period in 2013. Patient data was crossed with socioeconomic data (income and private health insurance status). Frequency tabulations and chi-square calculations were used to describe the patient mix, observe trends and appraise equity of admissions. Results: Analysis of the data showed that the number of patients from each neighbourhood relative to the neighbourhood population was equitable. However, when assessed on the basis of insurance status (i.e., deducting the population covered by private health insurance), a high level of inequity was detected (chi-square 71.828, df 3, p<0,0001) whereby patients from wealthier neighbourhoods were over represented compared to those from poorer neighbourhoods. Conclusion: This study has shown that access to the University Hospital in Brasilia is not equitable when individual access to private health care is accounted for. The results show that dual access to both public and private health care is likely to be common, increasing some of the population’s access to health care while decreasing access for others, and therefore contributing to inequity of access to health care services.